High Wave Events in The Java Sea to Support Maritime Transportation Safety - Triyono; Wilhelmina Patty; Johnny Budiman; Rose O.S.E. Mantiri; Billy Th. Wagey; Revols D. Ch. Pamikiran; Deiske A. Sumilat; Usman Efendi (Sam Ratulangi University, 2025)
The Java Sea plays a strategic role in supporting maritime transportation and trade in Indonesia, particularly as a key connector between Java Island and surrounding regions. However, the high intensity of maritime activity in this area is accompanied by a significant risk of maritime accidents, often triggered by high waves and extreme weather conditions. This study aims to analyze the characteristics of high wave events in the Java Sea to support maritime safety and disaster risk mitigation, in accordance with the SOLAS (Safety of Life at Sea) international standards. The analysis utilizes numerical wave model data from Wavewatch III and wind speed data from the Semarang Maritime Meteorological Station for the period of 2004–2023. The results reveal a bimodal annual pattern, with two peaks and two troughs in both wave height and wind speed cycles. Monthly occurrences of high wave events are most frequent in January and August. Annual trend analysis shows an increase of 1–2 events per year for waves with heights of 1.25–1.5 meters, and 1–3 events per year for waves of 1.5–2.5 meters. Meanwhile, waves exceeding 2.5 meters exhibit either a constant trend or statistically insignificant changes. These findings are expected to contribute to the development of early warning systems and policy frameworks aimed at enhancing maritime safety in the Java Sea region. Keywords: Java sea, high wave, wind speed, numerical model, SOLAS ABSTRAK Laut Jawa memiliki peran strategis dalam mendukung pelayaran dan perdagangan laut di Indonesia, khususnya sebagai penghubung utama Pulau Jawa dengan wilayah sekitarnya. Namun, tingginya intensitas aktivitas maritim di kawasan ini juga disertai dengan tingginya risiko kecelakaan laut, yang salah satunya dipicu oleh kondisi gelombang tinggi dan cuaca ekstrem. Penelitian ini bertujuan untuk menganalisis karakteristik kejadian gelombang tinggi di Laut Jawa sebagai upaya mendukung keselamatan pelayaran dan mitigasi bencana maritim, sejalan dengan standar internasional SOLAS (Safety Of Life At Sea). Analisis dilakukan menggunakan data model numerik Wavewatch III serta data kecepatan angin dari Stasiun Meteorologi Maritim Semarang selama periode 2004–2023. Hasil menunjukkan adanya pola dua puncak maksimum dan dua minimum dalam siklus tahunan tinggi gelombang dan kecepatan angin. Kejadian gelombang tinggi bulanan tertinggi terjadi pada Januari dan Agustus. Tren tahunan memperlihatkan peningkatan kejadian gelombang dengan ketinggian 1,25–1,5 m sebanyak 1–2 kejadian per tahun, serta gelombang 1,5–2,5 m sebanyak 1–3 kejadian per tahun. Sementara itu, gelombang lebih dari 2,5 m menunjukkan tren yang cenderung konstan atau tidak signifikan secara statistik. Temuan ini diharapkan dapat menjadi dasar dalam pengembangan sistem peringatan dini serta kebijakan keselamatan pelayaran di wilayah Laut Jawa. Kata kunci: laut Jawa, gelombang tinggi, kecepatan angin, model numerik, SOLAS